2020
DOI: 10.1186/s12871-020-01200-w
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative sedentary behavior is neither a risk factor for perioperative neurocognitive disorders nor associated with an increase in peripheral inflammation, a prospective observational cohort study

Abstract: Background Surgical interventions result in a postoperative rise in circulating inflammatory cytokines and high molecular group box protein 1 (HMGB1). Herein, the impact of a sedentary lifestyle and other age-related factors on the development of perioperative neurocognitive disorders (PND) following non-cardiac surgical procedures was assessed in an older (55–75 years-old) surgical population. Methods Prior to surgery, patients were asked questions regarding their sedentary behavior and daily habits. They al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…1,63 In fact, most clinical studies have shown that gender does not influence the development of PND. [64][65][66][67] In addition, basic studies did not consider the factor of gender, and male rats or mice were used. 68,69 In the present study, we used male mice to focus on the factor of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,63 In fact, most clinical studies have shown that gender does not influence the development of PND. [64][65][66][67] In addition, basic studies did not consider the factor of gender, and male rats or mice were used. 68,69 In the present study, we used male mice to focus on the factor of age.…”
Section: Discussionmentioning
confidence: 99%
“…PND is a complicated entity with subjective variability and numerous contributory factors, which are grouped into patient‐, surgical‐ and anaesthesia‐related factors, and for patient factors including age, educational level, mental health and comorbidities 1,63 . In fact, most clinical studies have shown that gender does not influence the development of PND 64–67 . In addition, basic studies did not consider the factor of gender, and male rats or mice were used 68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous pilot study on the effects of sedentary behaviour on development of PNDs in 38 surgical patients, mini-mental state examination (MMSE) scores (range 0e30) decreased from (mean [standard deviation]) 25.8 (4.2) at baseline to 23.6 (4.8) at 6 weeks after surgery (P<0.01). 6 An increase in pro-inflammatory markers was concomitantly observed during the first postoperative day; IL-6 levels increased from 31.2 (33.9) at baseline to 290 (277) pg ml À1 after 24 h, and HMGB1 levels increased from 38.9 (85.6) to 91.1 (170) pg ml À1 (P<0.0001). 6 A crucial question raised by this clinical study that evaluated both cognitive and biological assessments of surgical patients is whether or not development of PND, as reflected by a decline in the MMSE, can be predicted at an early juncture.…”
mentioning
confidence: 85%
“…6 An increase in pro-inflammatory markers was concomitantly observed during the first postoperative day; IL-6 levels increased from 31.2 (33.9) at baseline to 290 (277) pg ml À1 after 24 h, and HMGB1 levels increased from 38.9 (85.6) to 91.1 (170) pg ml À1 (P<0.0001). 6 A crucial question raised by this clinical study that evaluated both cognitive and biological assessments of surgical patients is whether or not development of PND, as reflected by a decline in the MMSE, can be predicted at an early juncture.…”
mentioning
confidence: 85%
“…Key inflammatory processes that were noted in animal models are also present in surgical patients. Shortly after surgical incision, circulating HMGB1 levels begin to rise ( Saxena et al, 2020 ) followed by an increase in pro-inflammatory cytokines ( Hirsch et al, 2016 ; Lammers-Lietz et al, 2022 ), disruption of the BBB ( Danielson et al, 2018 ), infiltration of monocytes into the brain ( Berger et al, 2019 ) and activation of microglia ( Forsberg et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%